The Influence Of Adaptive Work Behavior, Self-Efficacy And Employee Competence On Performance With Job Satisfaction As An Intervening Variable At The Personnel, Education, And Training Agency (BKPP) Of Banyuwangi Regency - Ikfina Himmati Aliya; Riyanto Setiawan Suharsono; Amalina Maryam Zakiyyah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to examine the influence of adaptive work behavior, self-efficacy, and employee competence on performance, with job satisfaction as an intervening variable at the Civil Service, Education, and Training Agency (BKPP) of Banyuwangi Regency. The research applied a quantitative method with descriptive and verificative approaches. From a population of 6,241 employees, a sample of 100 respondents was selected using the Slovin formula and purposive sampling technique. Data analysis employed Structural Equation Modeling Partial Least Squares (SEM-PLS) with SmartPLS 4.0 software. The results indicate that adaptive work behavior, self-efficacy, and competence each have positive and significant effects on both job satisfaction and employee performance. Job satisfaction also significantly affects performance. However, its mediating role is not consistently effective, as it does not significantly mediate between adaptive behavior or self-efficacy and performance. In contrast, competence positively influences performance through satisfaction. These findings suggest that strengthening competence and sustaining satisfaction are crucial strategies to enhance performance at BKPP Banyuwangi.